Use of Antibiotics against Bacterial Infections on Dairy Sheep and Goat Farms: Patterns of Usage and Associations with Health Management and Human Resources - Daphne T. Lianou; George C. Fthenakis (MDPI AG, 2022)
The objectives of the study were (a) to describe the patterns of antibiotic usage against four major clinical problems and (b) to evaluate factors that were associated with their use on small ruminant farms. Sheep and goat farmers mostly administered the antibiotics to animals at the dose prescribed (80.4%) and observed the necessary withdrawal period (98.7%), but fewer farmers (22.3%) weighed the animals to calculate their bodyweight before antibiotic administration. For the treatment of clinical mastitis, oxytetracycline, penicillin and streptomycin were the antibiotics used more frequently; 2.03 different antibiotics were used per sheep flock and 2.06 per goat herd, most frequently administered in injectable forms (88.8% of farms). In cases of abortion, oxytetracycline was administered more frequently; 1.12 different antibiotics were used per sheep flock and 1.03 per goat herd. In 94 farms (21.2%), routine administration of antibiotics was performed to newborns; oxytetracycline and ampicillin were administered more often. For the treatment of pneumonia in newborns, oxytetracycline, penicillin and tulathromycin were used more frequently; 1.33 antibiotics were used per sheep flock and 1.29 per goat herd. For the treatment of diarrhoea in lambs and kids, oxytetracycline, amoxicillin and penicillin were the antibiotics used more frequently; 1.34 antibiotics were used per sheep flock and 1.59 per goat herd. Results of multivariable analyses indicated 16 variables associated with the various outcomes for usage of antibiotics for the treatment of the above clinical problems. Of these, 11 variables were associated with the farmers: education of farmers was significant for three outcomes; the age, the experience, the professional involvement and farming family tradition of farmers and the daily period spent at the farm were each significant for one outcome.